Beautification of Pokhara City with a Special Focus on Phewa Lake and Lakeside Area - Khatiwada, Prashidha; Adhikari, Rabindra (Himalayan Journal of Applied Science and Engineering, 2021)
Pokhara is one of the rapidly growing cities of Nepal. It is the second-largest metropolitan city after Kathmandu. Because of the renowned temples, monasteries, lakes, adventure sports, and being close to the well-known Annapurna Range, it is considered as the tourism capital of Nepal. Millions of tourist visit this naturally gifted city every year contributing to considerable economic development. This economic prospect has attracted thousands of migrants every year leading to 67% growth in population in the last decade. The rapid population growth and urbanization without long-term planning and firm regulation have severely affected the development of sustainable infrastructure, preservation of the public space and natural resources. This has further impacted the tourism, economy, health and wellbeing, environment, and social aspect of the city. This article aims to generate strategies for retaining and improving the natural beauty of the city (focusing on the Phewa Lake area) by enhancing the economy and environment, rejuvenating social and cultural values, elevating the health and wellbeing of the people, and strengthening and promoting sustainable development. In this article, literature reviews, interviews, and field surveys were undertaken and four major improvements/developments are recommended for the beautification of Pokhara City. The recommendations are: preservation and development of open space into self-sustaining cohesive community parks, citizen-centred urban development, improvement of current transport infrastructure, and conservation of natural resources such as water, vegetation, and landscape.